Impact of capitation on physicians' behavior among patients with hypertension: an interrupted time series study in rural China - Jiani Zhang; Jincao Yan; Yunke Shi; Ning Zhang (BMC, 2024)
Abstract Objective The purpose of this study is to explore the change in physicians' hypertension treatment behavior before and after the reform of the capitation in county medical community. Methods Spanning from January 2014 to December 2019, monthly data of outpatient and inpatient were gathered before and after the implementation of the reform in April 2015. We employed interrupted time series analysis method to scrutinize the instantaneous level and slope changes in the indicators associated with physicians' behavior. Results Several indicators related to physicians' behavior demonstrated enhancement. After the reform, medical cost per visit for inpatient exhibited a reverse trajectory (-53.545, 95%CI: -78.620 to -28.470, p < 0.01). The rate of change in outpatient drug combination decelerated (0.320, 95%CI: 0.149 to 0.491, p < 0.01). The ratio of infusion declined for both outpatient and inpatient cases (-0.107, 95%CI: -0.209 to -0.004, p < 0.1; -0.843, 95%CI: -1.154 to -0.532, p < 0.01). However, the results revealed that overall medical cost per visit and drug proportion for outpatient care continued their initial upward trend. After the reform, the decline of drug proportion for outpatient care was less pronounced compared to the period prior to the reform, and length of stay also had a similar trend. Conclusion To some extent, capitation under the county medical community encourages physicians to control the cost and adopt a more standardized diagnosis and treatment behavior. This study provides evidence to consider the impact of policy changes on physicians' behavior when designing payment methods and healthcare systems aimed at promoting PHC.